HUBUNGAN CEDERA KEPALA DENGAN DISORIENTASI PADA PASIEN KECELAKAAN LALU LINTAS DI INSTALASI GAWAT DARURAT RS BHAYANGKARA AMBON - Dewi Arwini Bugis; Cosalina M Sangaji; Abdul Thalib (STIKES Pasapua Ambon, 2020)
Introduction : Head injury is a mechanical injury that directly or indirectly affects the head resulting in scalp injuries, skull fractures, tears in the lining of the brain, and damage to the brain tissue itself, as well as resulting in neurological disorders. The purpose of this study was to determine the relationship between head injury and disorientation in traffic accident patients at Bhayangkara Ambon Hospital Emergency Room. Method : This study used an analytic survey research design with a cross sectional study design. The population is 65 patients with a sample of all head injury patients who visited in the last year with age (15-55 years) by determining the number of samples using the Ishak and Michael formula tables. The sampling technique uses simple random sampling (probability sampling). The intervention process uses a questionnaire. Result :The results of the study with the Chi Square test (α = 0.001) show that (0.001 <0.05), then H1 is accepted or there is a relationship between head injury and disorientation. Conclusion : The conclusion of this study is that there is a relationship between head injuries and disorientation.